Recurrent Focal Segmental Glomerulosclerosis: A Discrete Clinical Entity. (11th January 2012) - Torban, Elena; Bitzan, Martin; Goodyer, Paul
Abstract : Focal segmental glomerulosclerosis refers to a set of particular histopathologic lesions in which steroid-resistant podocyte injury leads to patchy adhesions between the glomerular tuft and Bowman's capsule, followed by progressive glomerulosclerosis and proteinuric renal failure. Because of the nonspecific nature of this lesion, it has been difficult to classify the various forms of primary nephrotic syndrome in children. However, with the recognition of hereditary FSGS caused by mutations podocyte slit diaphragm genes, it is increasingly clear that the steroid-resistant form of FSGS that recurs in the renal allografts (R-FSGS) constitutes a distinct clinical entity. Capitalizing on recent studies in which patients have been screened for slit diaphragm gene mutations, this review focuses on the natural history and pathogenesis of R-FSGS.